Analysis theorico-practica de viribus virus febriferi, pestiferi, atque serpentin : the first medical article by an author from Bosnia and Herzegovina = Analysis theorico-practica de viribus virus febriferi, pestiferi, atque serpentin : prvi medicinski članak autora iz Bosne i Hercegovine - Delibegović, Samir (Array, 2021)
This review describes the first medical article written by an author from Bosnia and Herzegovina. The article was published by Fr. Franjo Gracić (1740-1799), in Latin, under the title: "Analysis theorico-practica de viribus virus febriferi, pestiferi, atque serpentin", and printed in Padua in 1795, translated as: "A Theoretical and Practical Presentation of the Effects of Fevers, Infectious Diseases, and Snake Poison". From today"s standpoint, it may be said that it was a review article about some of the most frequent diseases of that time. The paper is of exceptional importance for the history of medicine in Bosnia and Herzegovina because it is the first documented medical article whose author was from Bosnia and Herzegovina. The paper contains observations of the course of diseases and treatment, in line with the medical insights of the time. The author refers to the authorities of that time, such as Samuel Auguste André Tissot, the Swiss physicist and doctor, Georg Bauer, the German doctor, and Lodovico Antonio Muratori, the Italian scholar, which makes this article a link between Bosnia and Herzegovina and the knowledge of the Europe of that time. This paper represents the beginning of medical writing in Bosnia and Herzegovina and has a very important place in the history of medicine in this country.